Citation analysis for core journals in educational leadership. Issue 1 (4th January 2016) - Griffin, Karin L
Abstract : Purpose: – The purpose of this paper is to establish a core serials list for "Single doctoral", Carnegie classification universities offering Doctor of Education (EdD) programs in educational leadership based on a sample of six institutions over a six-year period. Design/methodology/approach: – A citation analysis was used using a descriptive research design. The population was all dissertations accepted for the award of the EdD degree in Educational Leadership from 2005 to 2010 at six peer institutions. From this population, 20 dissertations from each institution were randomly selected during the period under study. Data were extracted from the title pages and reference lists. Extracted data were analyzed using descriptive statistics. Serial titles were ranked according to a frequency-weighted index formula, which recorded the serial titles cited by the greatest percentage of students. Findings: – It was found that the serials with the highest frequency weight depended, in part, on the period studied. The findings also showed that 84.2 per cent of the serial citations were represented by four Library of Congress classification areas: education (L); social sciences (H); medicine (R) and philosophy, psychology and religion (B). In addition, it was found that EdD students cited serials aged 10 years or less more than other sources of information materials. Originality/value: – While other citation analyses of dissertations have been done, including some that compare dissertations at more than one institution, the author could find no other study of EdD dissertations, specifically, across a nationwide group of peer institutions. Further, the author could find no other citation analysis covering as many as six continuous years, which made a difference in the most frequently cited serial titles.